2016
DOI: 10.1002/ca.22783
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy, radiology, and practical procedure education for foundation doctors in England: A National Observational Study

Abstract: There are concerns regarding the anatomy knowledge amongst medical school graduates and foundation doctors. Clinical procedures performed without relevant anatomical knowledge could result in serious harm to patients. The aim of this quantitative study was to assess education provision in the domains of anatomy, radiology and practical procedures for foundation year doctors during their first two years of training (FY1, FY2). A national survey of acute hospital trusts in England was conducted. Each trust compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In healthcare degree programmes, anatomy modules are generally taught at the beginning as an essential component of health education in order to ground basic knowledge in areas such as histology and gross anatomy, among others (Brown et al, 2017;Reinke, 2019). Indeed, without this knowledge, healthcare providers may be unable to effectively develop their clinical practice (Lewis et al, 2016). Although some anatomy-related teaching approaches have traditionally included various strategies such as cadaver dissection or the use of anatomical models (Choi-Lundberg et al, 2016;Ghosh, 2017;Pais et al, 2017), new teaching approaches have recently been studied, including prosected specimens (Mitrousias et al, 2020), computer-aided instruction (Wilson et al, 2019), educational websites (Natsis et al, 2021); bodypainting (Diaz and Woolley, 2021), integrated problem-based learning cases (Doomernik et al, 2017), brainstorming (Goswami et al, 2017), and even effective use of the museum (Kim et al, 2017;Memon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In healthcare degree programmes, anatomy modules are generally taught at the beginning as an essential component of health education in order to ground basic knowledge in areas such as histology and gross anatomy, among others (Brown et al, 2017;Reinke, 2019). Indeed, without this knowledge, healthcare providers may be unable to effectively develop their clinical practice (Lewis et al, 2016). Although some anatomy-related teaching approaches have traditionally included various strategies such as cadaver dissection or the use of anatomical models (Choi-Lundberg et al, 2016;Ghosh, 2017;Pais et al, 2017), new teaching approaches have recently been studied, including prosected specimens (Mitrousias et al, 2020), computer-aided instruction (Wilson et al, 2019), educational websites (Natsis et al, 2021); bodypainting (Diaz and Woolley, 2021), integrated problem-based learning cases (Doomernik et al, 2017), brainstorming (Goswami et al, 2017), and even effective use of the museum (Kim et al, 2017;Memon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the current curriculum at MU, no separate anatomical tests are used to test the students' anatomy knowledge. Another reason that could possibly explain a deficiency in knowledge is a lack of time to teach anatomy (Bergman et al, 2011;Lewis et al, 2016). Anatomy is often difficult to learn and therefore investment in study time is necessary (Bergman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An observational study 25 of foundation doctors in the UK found the average hours dedicated to radiology education each year was 10.5 and 7.8 h for years 1 and 2, respectively, although this varied between sites. Hypothesised reasons included lack of time, inadequate facilities, unavailability of teaching staff, limited financial resources and absence of specific inclusion of radiology within the junior doctor curriculum.…”
Section: Medical Imaging Knowledge and Education For Different Non-radiologist Clinician Groupsmentioning
confidence: 99%